Extração de compostos fenólicos assistida por ultrassom e determinação de ácidos graxos e minerais em folhas de Olea europaea L. - Cavalheiro, Caroline Viegas (2013)
Olive leaves are an agricultural by-product generated by the pruning of trees. Recently, it was reported that these leaves have high levels of phenolic compounds with biological activity, which increase the interest of both academic and economic exploitation in relation to the their use for feed and food. However, few information is available regarding to the presence of other nutritional compounds, such as fatty acids and mineral elements. Thus, this study aimed to determine the fatty acids profile and also different elements present in different varieties of olive leaves grown in southern Brazil, as well as develop a procedure for extraction of phenolic compounds with the aid of ultrasound, using a low-toxicity solvent (ethanol 60 % v/v, with 1 g L-1citric acid), and compare it with the traditional extraction method of extraction (maceration) to its future application in food products. For varieties studied, Ascolano, Arbosana, Negrinha do Freixó, Koroneiki and Grappolo concentrations of ash, protein, lipid and total carbohydrates levels ranged from 4.37% to 6.00%, 10.50% to 13.10%, 9 13% to 9.80% and 8.74% to 32.63%, respectively. The variety Arbosana showed the highest concentration of phenolic compounds when was carried out one extraction followed by re-extraction by maceration (35.71 mg GAE g-1), and the highest concentration of saturated fatty acids (total of 37.26%, composed by 1.54 ± 0.04% myristic acid, 26.90 ± 0.50% palmitic acid, 5.55 ± 0.14% stearic acid and 3.26 ± 0.13% arachidic acid). The varieties Ascolano, Koroneiki and Grappolo had the highest amounts of fatty acids considered beneficial to health (68.03%, 68.63% and 68.18% respectively, data for the sum of fatty acids oleic, linoleic and linolenic). The Ascolano variety showed generally higher concentrations of most minerals determined. The elements present in highest concentration in the five varieties studied were Al, Ca, Fe, K, Mg, P and S, but the levels found for Fe, Cu, Zn, Mn, and Ca were more significant in relation to the recommended daily intake. All these results show the importance of the formation of these varieties which can be used as supplements in the feed. In the extraction of phenolics from Arbequina variety assisted by ultrasound were optimized the position of the probe (1 and 3 cm), the extraction temperature (20 °C, 40 °C and 60 °C) and the extraction time (0.5 - 20 min), using 40% amplitude and 20 kHz frequency. The results showed that the use of 20 °C during 20 min for extraction lead to 75.33% of recovery of phenolic compound (20.50 ± 0.26 mg GAE g-1) when compared with the conventional method of extraction (maceration, 22 °C, 5 h, 27.32 ± 0.90 mg GAE g-1). The position of the probe did not significantly affect the results and the main effect caused by the ultrasound was stirring. Thus, we developed a fast and effective method of extraction, confirming the benefits of using ultrasound to obtain extracts from natural sources.